A large, X-shaped polyoxometalate [As6Fe7Mo22O98]25− assembled from [AsMo7O27]9− and [FeMo4O19]11− moieties. Issue 44 (30th October 2018) - Wu, Panfeng; Zhang, Yanping; Feng, Caiting; Liu, Bin; Hu, Huaiming; Xue, Ganglin
Abstract : The X-shaped polyoxometalate contains a unique heptanuclear iron cluster with a spin ground state of S = 7.5. Abstract : A large X-shaped polyoxometalate, [As6 Fe7 Mo22 O98 ] 25− (1 ), has been synthesized and structurally characterized. The skeleton of1 is composed of two monocapped hexavacant Keggin [AsMo7 O27 ] 9− units and two divacant Anderson [FeMo4 O19 ] 11− units fused together through a central Fe5 O4 core and two μ4 -As2 O bridging units, resulting in a unique tetramer with C 2h symmetry. The polyanion represents the largest iron-containing arsenomolybdate to date and it contains an unprecedented heptanuclear iron(iii ) cluster. The investigation of the magnetic properties shows that the Fe7 cluster exhibits an overall ferromagnetic interaction with a spin ground state of S = 7.5.